Obesity as a risk factor for oxidative damage to membrane lipids in postmenopausal women - Szosland, Janusz; Kokoszko, Agnieszka; Zasada, Krzysztof; Stępniak, Jan; Lewiński, Andrzej; Karbownik-Lewińska, Małgorzata (Menopause Review/Przegląd Menopauzalny, 2010)
Introduction: Obesity does constitute one of the most common modifiable risk factors for cancer, with further increase in the risk in postmenopausal women. In turn, the process of cancerogenesis is associated with the enhanced oxidative stress. Lipid peroxidation (LPO), resulting from oxidative damage to membrane lipids, is the most frequently examined process to evaluate oxidative damage to macromolecules. Aim of the study: The aim of the study was to evaluate the LPO level in overweight and obese postmenopausal women. Materials and methods: Forty two postmenopausal women, i.e. 35 overweight or obese with a body mass index (BMI) ł 25 kg/m 2 , and 7 with BMI < 25 kg/m 2 (Controls), well matched for age, were enrolled in the study. Concentration of malondialdehyde + 4-hydroxyalkenals (MDA + 4-HDA), as an index of LPO, was measured in the serum. Clinical and laboratory parameters, which are frequently affected by obesity, were also measured in the study. Results: The LPO level increased in overweight and obese postmenopausal women and its further increase was observed with the increasing BMI. Additionally, the LPO level correlated positively with body mass, BMI, waist or hip circumference and waist: hip ratio (WHR). Body weight was the only independent positive predictor for increased oxidative stress. In turn, the LPO level was the only independent positive determinant for obesity. Conclusions: Increased body mass does contribute directly to enhanced oxidative damage to membrane lipids in postmenopausal women, a phenomenon which may constitute one of the mechanisms of an increased cancer risk.